2020
DOI: 10.1055/s-0040-1720976
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Central Venous Access Device-Related Thrombosis in Hospitalized Children: A Systematic Review and Meta-Analysis

Abstract: Objective To identify the potential associations of patient-, treatment-, and central venous access device (CVAD)-related factors with the CVAD-related thrombosis (CRT) risk in hospitalized children. Methods A systematic search of PubMed, EMBASE, Web of Science, the Cochrane Library, China National Knowledge Infrastructure, Wanfang, and VIP database was conducted. RevMan 5.3 and Stata 12.0 statistical software were employed for data analysis. Results In terms of patient-related factors, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 42 publications
(33 reference statements)
0
7
0
Order By: Relevance
“… [15] Risk factors associated with CLABSI include the duration of central lines, the use of central lines to draw blood, peripherally inserted rather than tunnelled lines, and if femoral sites are used for line insertion. [16 , 17] In recognition of CLABSI as an important preventable hospital-acquired infection, the ‘Best Care Always!’ (BCA) campaign was launched to focus the efforts of healthcare workers on preventative measures in the form of bundles of care. [18] In one of the longest-running intervention studies related to CLABSI in SA, Richards et al [19] evaluated the impact of improved compliance to a CLABSI prevention bundle on the CLABSI rate in a private hospital group.…”
Section: Discussionmentioning
confidence: 99%
“… [15] Risk factors associated with CLABSI include the duration of central lines, the use of central lines to draw blood, peripherally inserted rather than tunnelled lines, and if femoral sites are used for line insertion. [16 , 17] In recognition of CLABSI as an important preventable hospital-acquired infection, the ‘Best Care Always!’ (BCA) campaign was launched to focus the efforts of healthcare workers on preventative measures in the form of bundles of care. [18] In one of the longest-running intervention studies related to CLABSI in SA, Richards et al [19] evaluated the impact of improved compliance to a CLABSI prevention bundle on the CLABSI rate in a private hospital group.…”
Section: Discussionmentioning
confidence: 99%
“…In Europe, carboPEI 7,8 is delivered with large volumes of intravenous hydration, can exacerbate pre‐existing DI, particularly where no thirst mechanism is present, and is associated with prolonged inpatient admissions 20 . Such chemotherapy schedules are also associated with short‐ 8 and long‐term 11–13,16 toxicities and, moreover, require central venous access devices for delivery, with associated infection and thrombosis risk 14,15 . A further UK intracranial germinoma case, in addition to the two formally described here, received two vinblastine doses to complete induction as a “bridge” to radiotherapy with stable radiological appearances; this patient developed ifosfamide encephalopathy 23 during standard‐of‐care carboPEI chemotherapy and experienced a fall and subdural hematoma.…”
Section: Discussionmentioning
confidence: 99%
“…Long‐term sequelae of these drugs include ototoxicity from cisplatin 11 and reduced fertility from alkylating agents (ifosfamide) 12,13 . Current chemotherapy regimens also require the use of indwelling central venous access devices, which are associated with increased risk of infection 14 and thrombosis 15 and which may affect quality of life. In North America, the standard‐of‐care schedule to reduce radiotherapy treatment volume and/or dose is carboplatin–etoposide 9 .…”
Section: Introductionmentioning
confidence: 99%
“…The subsequent highest incidence was in hematological tumor patients (6.97%). Immunomodulators and hormones may lead to an increased risk of CRT [13,27]. In addition, patients with hematological tumors have higher use of recombinant human granulocyte stimulating factors, which decreases leukocytes and neutrophils, contributing to an increased risk of thrombosis [28].…”
Section: Figure3 Auc (95% Ci) Plots Of 3 Prediction Modelsmentioning
confidence: 99%
“…Studies have shown that previous venous thromboembolism (VTE) history [10], catheterization history [11], trauma history [7], higher level of D-dimer [11], and catheter-related infection [10] are risk factors for CRT in cancer patients in terms of patient-related factors. In the catheterization factors, CRT is closely related to the puncture method (with the help of visualization technology) [12] and the puncture site [13]. In terms of catheter-related factors, studies have shown that catheter type [14], catheter lumens [10], ratio of catheter diameter to vessel diameter [15], and position of catheter tip are related to CRT [14].…”
Section: Introductionmentioning
confidence: 99%